A new heterocyclic Schiff base and its metal complexes - Sönmez, M; Sekerci, M (Marcel Dekker Inc, 2004)
Cu(II), Co(H), Ni(II), and Zn(II) metal complexes of a new SNO tridentate heterocyclic Schiff base derived from the reaction of 1-amino-5benzoyl-4-phenyl-IH-pyfimidine-2-thione with salicylaldehyde have been synthesized and characterized on the basis of elemental analyses, electronic, IR, and H-1 NMR spectra, and also by molar conductivity measurements, magnetic moment measurements and thermogravimetric analyses (TGA). It has been found that the Schiff base behaves as a neutral tridentate SNO ligand forming chelates with I : 2 or I : I (metal: ligand) stoichiometry. The complexes of Co(II), Ni(II), and Zn(II) are proposed to have an octahedral structure, while the Cu(II) complex is suggested to have a square-pyramidal geometry. All of the complexes show nonelectrolytic behavior.
Keywords: synthesis; salicylaldehyde Schiff base; binuclear complexes; pyrimidine-2-thione